Comparative Study of Antioxidant Levels (Vitamin E &Selenium) In Serum of Polycystic Ovary Syndrome Patients and Control - Hamad, Abdul Wahab Rzwki; Ahmad, Salman Ali; Rasheed, Farah Aqeel (Al-Nahrain Journal of Science, 2018)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder of reproductive women. The antioxidant (Vitamin E and Selenium) have important role in infertility and in PCOS. The aim of this study, to know the role of Vitamin E and Selenium during the phases of menstrual cycle and its effect on ovulation in (PCOS) patients and effect of body mass index in PCOS patients. This study, include 25 untreated and 26 treated PCOS patients comprised with 42 control. Vitamin E and selenium were measured by high performance liquid chromatography (HPLC) and atomic absorption spectrophotometer (AAS), respectively. Our results were observed vitamin E have significant (p